Radical Democracy - Sánchez Santiago, Alfredo (EUNOMÍA. Revista en Cultura de la Legalidad, 2024)
The aim of this work is to distinguish radical democracy from other currents in contemporary democratic theory and to review some of the authors and approaches that have given shape to this notion in political philosophy over the last few decades. In the first part, I situate the concept of radical democracy in the context of counter-hegemonic struggles that unfold in various geographies following the financial crisis of 2008 and assess our current distance from that period of political effervescence. Subsequently, I outline a brief conceptual history of radical democracy from the 1960s to the 1990s and argue for the need to inscribe radical democracy in the lineage of the modern democratic revolution. I propose, finally, three very basic traits to articulate a minimal definition of the concept. I conclude by highlighting some contradictions facing the project of radicalizing democracy in the second decade of the 21st century.
Keywords: Agonistic democracy; liberal democracy; social movements; political participation; equality; representative democracy; deliberative democracy; hegemony; post-Marxism; conflict